2021
DOI: 10.1055/s-0041-1726407
|View full text |Cite
|
Sign up to set email alerts
|

Flexor Carpi Radialis Brevis Resection for Treatment of a Distal Radius Fracture: A Case Report

Abstract: The flexor carpi radialis brevis (FCRB) is an anomalous muscle of the forearm that is only present in 3.5 to 8.6% of the population. In the case of volar plating of distal radius fractures, the FCRB inhibits proper fracture exposure and thus hinders proper reduction. A 78-year-old female presented with right distal radius fracture which necessitated internal fixation. Following mobilization and retraction of the flexor carpi radialis tendon, an anomalous muscle belly was identified as the FCRB. With continued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…Laugharne and Power stated that the FCRB made the exposure of the distal radius more difficult, and that distal release was necessary to visualize the fracture site [ 14 ]. Werntz et al showed that the FCRB was resected because its retraction to expose and reduce the fracture site was difficult [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Laugharne and Power stated that the FCRB made the exposure of the distal radius more difficult, and that distal release was necessary to visualize the fracture site [ 14 ]. Werntz et al showed that the FCRB was resected because its retraction to expose and reduce the fracture site was difficult [ 15 ].…”
Section: Discussionmentioning
confidence: 99%